CONCEPT AND IMPLEMENTATION OF RELIGIOUS MODERATION IN INDONESIA - Khairan M Arif (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
Religious moderation became a very important narrative and concept in the global era, facing the rise of radicalism and religious and ideological liberalism. The purpose of this research is to provide the concept and strategy of implementation of religious moderation in Indonesia, with the approach of Islam and the Constitution of the Republic of Indonesia that is pancasialis and religious. The type of method used in this research is Qualitative method with Library Research approach by analyzing in depth primary and secondary references about religious moderation and moderation in Islam. The results of this Study gave birth to several concepts, first; Moderate understanding and attitude is a middle attitude that avoids extremities and or liberality, fair and proportionate in understanding and practicing religious teachings for its participants and moderation is the best understanding and attitude in human life both according to Islamic sources and social philosophers. Secondly; In Islam moderation is the understanding and attitude of the middle or fair, balanced and proportionate in religion. Moderasi beragama menjadi narasi dan konsep yang sangat penting di era global, menghadapi maraknya radikalisme dan liberalisme agama dan ideologi. Tujuan penelitain ini adalah memberikan konsep dan Srategi Implementasi Moderasi beragama di Indonesia, dengan pendekatan Islam dan Konstitusi Negara Republik Indonesia yang pancasialis dan religius. Jenis metode yang digunakan dalam penelitian ini adalah metode Kualitatif dengan pendekatan Library Research dengan menganalisa secara mendalam referensi-referensi Primer dan sekunder tentang Moderasi beragama dan moderasi dalam Islam. Hasil Peneltian ini melahirkan beberapa konsep, pertama; Paham dan sikap moderat adalah Sikap pertengahan yang menghindari ekstrimitas dan atau liberalitas, adil dan proporsional dalam memahami dan mengamalkan ajaran agama bagi pemeluk-pemeluknya dan moderasi adalh paham dan sikap terbaik dalam kehidupan manusia baik menurut Sumber-sumber Islam maupun para filosof sosial. Kedua; Dalam Islam Moderasi adalah paham dan sikap pertengahan atau adil, seimbang dan proporsional dalam beragama.